ORGANIZATIONAL, MANAGERIAL AND LEGAL ASPECTS OF MEDIA BUSINESS FUNCTIONING IN MODERN CONDITIONS - Г. М. Дергачова; Є. В. Дергачов (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The article analyzes the current state of the media market in Ukraine, highlights the trends in the functioning of media enterprises. The purpose of the research is to analyze the current state of the media business, to highlight the organizational, managerial and legal aspects of the functioning of media enterprises and to outline the problematic aspects of their activities in the modern conditions of rapid technological development. The organizational and legal forms of creating media enterprises are analyzed. The advantages of organizing the holding form of media business as a structure that is better able to resist the influence of destabilizing factors and respond mobile to changing trends in the information market are highlighted. Singled out media market participants in accordance with the new media legislation and requirements for them. Emphasis on the criteria that allow the media to be classified as an online media.